Answer:
(-6, 8)
Step-by-step explanation:
(x, y) --> (-y, -x)
(-8, 6) --> (-6, 8)
Therefore, (-6, 8)
I hope this helped and have a good rest of your day!
Answer:
Ok soo.
Step-by-step explanation:
sum of two adjacent angles of parallelogram is 180
so angle K + angle L = 180
as AK bisects angle K and LA bisects angle L
so, angle AKL + angle ALK = 180 /2 = 90
in triangle AKL,
angle AKL + angle ALK+angle KAL = 180(sum of all angles in triangle = 180)
so, from above two equations,
angle KAL = 90
_____________________________________________
❂✨Answered By Tokyo ✨❂
❉ Brainliest Would Be Appreciated❉
✯If You Have Questions Ask In the Chat Box✯
Answer:
-10.27
Step-by-step explanation:
-7.54-1.98=-9.52, and -9.52-0.75=-10.27
Answer:
The ones that can be used are (B and A)
The ones that cannot be used are (C and D)
Step-by-step explanation:
Because the panthers got 6 less and the tigers got 22…
b+6 would make 22 (panthers plus 6 makes tigers)
22-b would also be 6 because 6+b makes 22, so subtracting b from 22 makes 6
Answer:
10
Step-by-step explanation: